Energy expenditure and food intake of competitive swimmers during training - Soultanakis, H.; Mandaloufas, M.; Platanou, T. (Biomechanics and Medicine in Swimming X, 2006)
Poor dietary practices may accumulate and lead to deficiencies that may influence performance during training. The purpose of this study was to investigate weather the dietary intake of elite swimmers can match the energy and nutrient requirements of training. Dietary habits were evaluated in 16 elite swimmers (6 male, 10 female). Diet content and energy expenditure were estimated by using 3-day weighed dietary and activity records. Their three day training averaged 7.568 m of swimming per day. The total energy cost averaged 3146.88±494.10 kcal/day. Diet records revealed that the swimmers consumed daily 2182.25 ± 964.14 kcal/day, approximately 800 kcal less than their daily requirements. Protein intake was approximately double their energy cost. The results demonstrated the inability of swimmers to maintain a balanced diet.